2016
DOI: 10.18538/lthe.v13.n1.221
|View full text |Cite
|
Sign up to set email alerts
|

An examination of cultural bias in IELTS Task 1 non-process writing prompts: a UAE perspective

Abstract: This study analyzed 24 IELTS Task One (data explanation) prompts for task type, diagram type, subject matter, level of critical thought, and geographical references, in order to determine whether Emirati university students' anecdotal claims of cultural bias on the IELTS academic writing exam (as experienced by the researcher in the past decade of teaching IELTS in the United Arab Emirates) are valid. The analysis found that the majority of the task types (88%) were non-process in nature (i.e. required the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Relatedly, Uysal (2010) showed that the target language use domains of IELTS writing tasks have been limited British and Australian contexts which seriously question meaningfulness and representativeness of IELTS interpretations. In a later study, Freimuth (2016) reported culturally biased unfamiliar Western notions of IELTS reading for Emirati students. More recently, Jenkins and Leung (2019) criticized the utilization of mainly American or British culture, social conventions, idiomatic language, or locations in the IELTS writing tasks type I, which may disadvantage those without deep knowledge of America.…”
Section: Introductionmentioning
confidence: 93%
“…Relatedly, Uysal (2010) showed that the target language use domains of IELTS writing tasks have been limited British and Australian contexts which seriously question meaningfulness and representativeness of IELTS interpretations. In a later study, Freimuth (2016) reported culturally biased unfamiliar Western notions of IELTS reading for Emirati students. More recently, Jenkins and Leung (2019) criticized the utilization of mainly American or British culture, social conventions, idiomatic language, or locations in the IELTS writing tasks type I, which may disadvantage those without deep knowledge of America.…”
Section: Introductionmentioning
confidence: 93%
“…The average IELTS scores in 2017 from testing centres in those countries are mostly well below 7.0: 5.76 (China), 6.04 (India), 6.65 (Brazil), 6.71 (France), 6.12 (Brazil), 6.79 (Nigeria), 5.81 (Japan), and 5.26 (Saudi Arabia). A variety of factors might infl uence this variation: Those who have critically examined the IELTS test have found issues of cultural bias (Khan, 2006;Freimuth, 2016), economic factors (Hamid, 2016), and linguistic factors (Uysal, 2010), and other phenomena that might account for these national pa erns in test performance. The statistics above are general national statistics, and also IELTS is but one path into Canadian universities.…”
Section: Looking Beyond 65?mentioning
confidence: 99%
“…Teachers considered the IELTS and TOEFL, which are products of the UK and the USA respectively, as fairly good indicators of students' proficiency. Several authors highlighted the economic and political ideologies underlying the IELTS and TOEFL (Khan, 2009;Templer, 2004), their cultural biases and unsuitability for different contexts (Al-Issa, 2016;Khan, 2009;Templer, 2004), their lack of validity (Al-Malki, 2014;Freimuth, 2016) and reliability (Alshammari, 2016). Hence, teachers at the ELCs need to be aware of these critical issues and their potential consequences and work towards utilizing alternative assessments since these two tests are high-stakes tests and much rests on the scores students obtain (Al-Issa, 2016).…”
Section: 45mentioning
confidence: 99%